THE EFFECT OF USING GRAPHIC ORGANIZERS TECHNIQUE ON STUDENTS’ WRITING RECOUNT TEXT ABILITY - Asriani Hasibuan; Gabby Maureen Pricilia; Derliana Hasibuan; Amris Tumanggor (Institut Pendidikan Tapanuli Selatan, 2022)
This study aims to determine the extent to which the use of graphic organizer techniques in teaching students to write in recount texts, the extent to which students' writing skills in recount texts before and after using graphic organizer techniques, and to determine whether there is a significant effect between graphic organizer techniques on writing skills. students in the recount text at class X SMA Negeri 1 Manduamas. This research was conducted using an experimental method (pretest posttest one group design) with a sample of 26 students and taken by purposive sampling technique from 2 classes as the population. Tests and questionnaires were used in data collection. Based on data analysis, it can be seen that the average use of the graphic organizer technique in students' learning to write in recount text is 79 with the